COMPETIVINESS OF SERBIAN FOOD INDUSTRY IN PRODUCT AND PACKAGE DESIGN - Radojevic, Predrag D.; Marjanovic, Darko (Economics of Agriculture, 2011)
This paper is an attempt to indicate on one of the options for strengthening the competitiveness of the domestic food industry. This possibility is founded in the recognition of product design and packaging as an important factor in competitiveness. In order to determine the extent to which food industry in Serbia believe that the product design and packaging is a factor of competitiveness, a research was undertaken. The basic hypothesis in research was that the reason for bad competitiveness may be conservative attitude toward design, insufficient investment and lack of incentives. The research included the perception of design as a factor of competitiveness, the practice of food industry in this field, and comparation of this data with data from other industries. Data collected by the empirical research enabled the confirmation of the basic hypothesis. They also gave the recommendations that the enterprises in food industry and creators of development strategies and economic policies should pay special attention on product design and packaging if they want to improve the competitiveness.